A Formal Verification-Based Risk Scoring System for Code-Level Vulnerabilities in Critical Applications - Paidy, Pavan (International Journal of Applied Mathematical Research, 2025)
This paper presents a novel framework for addressing code-level vulnerabilities in critical applications by combining formal verification with risk scoring systems. It ensures the correctness and reliability of code while prioritizing vulnerabilities based on exportability and impact. The approach is applied to high-stakes industries such as healthcare, aerospace, and industrial control, where system failures can have catastrophic consequences. A numerical example demonstrates a 22% reduction in risk (from 1.905 to 1.485) within budgetary constraints. Results show that this combined method offers a robust, cost-efficient solution for improving security, making it practical for real-world deployment. The framework emphasizes risk reduction and cost optimization in resource-constrained environments.